PENGEMBANGAN MODEL PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KARAKTER ILMIAH SISWA SMP - Muhammad Agus Martawijaya (Journal of Educational Science and Technology (EST), 2015)
ABSTRACTIndonesia is experiencing a crisis that led to the occurrence of horizontal conflicts among its citizens. This crisis is an indication that the characters of Indonesian people declined and deviated from the appreciation and the practice of Pancasila’s values as a foundation of the Republic of Indonesia (RI). To overcome this problem, the local wisdom as a cultural element must be integrated into learning process to enhance the scientific characters of students such as honesty. This is a steering normative for character education in schools or educational unit. A’bulo sibatang is one of the local wisdom which still exists and upheld in Barrang Lompo Island’s community and a rudimentary foundation to build a model of learning based on local wisdom. Learning physics model based on this local wisdom met the criteria of validity and practicality, and was found to increase the scientific honesty of students effectively. This model can be applied to any other place in accordance with the characteristics of the study site, the subject of research, and the educators who will become educator’s model.